Langerhans cell histiocytosis in sequential discordant lymphoma - Adu-Poku, K (Copyright 2005 Journal of Clinical Pathology, 2005)
B cell non-Hodgkin lymphoma of the follicular subtype (grade 3/3) affecting the nasopharynx and breast, and containing foci of Langerhans cell histiocytosis, was diagnosed in a 56 year old white woman who was a longstanding heavy smoker. Four years before this she had developed stage 1a mixed cellularity Hodgkin lymphoma affecting the right inguinal region, which was treated by irradiation and chemotherapy without recurrence. Review of the original Hodgkin lymphoma histology demonstrated a small focus of Langerhans cell histiocytosis. This is thought to be the first recorded case of Langerhans cell histiocytosis occurring in a sequential discordant lymphoma. Its importance is discussed.